Pengembangan Media Pembelajaran Dinasti Abbasiyah Berbasis Smartphone Untuk Meningkatkan Pemahaman Siswa Kelas XI MA - Fauzi, Fakhri; Jennah, Rodhatul; Rohmadi, Mukhlis (JKTP: Jurnal Kajian Teknologi Pendidikan, 2025)
The teaching of Islamic Cultural History (SKI) at Madrasah Aliyah Miftahul Jannah Palangka Raya often faces challenges in attracting students' interest. The learning media used tends to be conventional, making it less suitable for the needs of the current digital generation. The research aims to develop smartphone-based learning media designed to enhance the quality and understanding of SKI learning.The research uses the Research and Development method with the define, design, develop, disseminate approach, which consists of definition, design, development, and dissemination. The development process involves expert validation, testing, and revision to ensure the media's feasibility. The research results show that the developed application is capable of facilitating more interactive and engaging learning for students.In conclusion, smartphone-based learning media is effective in enhancing students' interest and understanding of Abbasid dynasty material. Additionally, the media can also serve as an innovative alternative in technology-based learning in line with the needs of modern education. Abstrak Pembelajaran Sejarah Kebudayaan Islam (SKI) di Madrasah Aliyah Miftahul Jannah Palangka Raya sering kali menghadapi kendala dalam menarik minat peserta didik. Media pembelajaran yang digunakan cenderung konvensional sehingga kurang sesuai dengan kebutuhan generasi digital saat ini. Penelitian bertujuan mengembangkan media pembelajaran berbasis smartphone dirancang untuk meningkatkan kualitas dan pemahaman pembelajaran SKI. Penelitian menggunakan metode penelitian dan pengembangan (Research and Development) dengan pendekatan define, design, develop, disseminate terdiri dari pendefinisian, perancangan, pengembangan, penyebaran. Proses pengembangan melibatkan validasi ahli, uji coba, dan revisi memastikan kelayakan media. Hasil penelitian menunjukkan aplikasi yang dikembangkan mampu memfasilitasi pembelajaran lebih interaktif dan menarik bagi peserta didik. Kesimpulannya, media pembelajaran berbasis smartphone efektif dalam meningkatkan minat belajar dan pemahaman peserta didik materi dinasti Abbasiyah. Selain itu, media juga dapat menjadi alternatif inovatif dalam pembelajaran berbasis teknologi sesuai dengan kebutuhan pendidikan modern.